Large Lipomatous Hypertrophy of the Interventricular Septum - Ak, Koray (Texas Heart® Institute, Houston, 2014)
We present the case of a 58-year-old woman who had large lipomatous hypertrophy of the interventricular septum, a condition that is reported very infrequently. Preoperative cardiac magnetic resonance images revealed an inhomogeneous, infiltrating mass that was suppressed in fat-suppression mode. The extensive mass was causing right ventricular dysfunction, so we excised it through a right ventricular approach. The findings on histologic analysis of the mass were consistent with lipomatous hypertrophy. The patient died of septic shock on the 28th postoperative day. In addition to the patient's case, we discuss the characteristics and diagnosis of this rare entity.